Os Primeiros Anos da Pedagogia de Rio Claro - Marilena A. Jorge Guedes de Camargo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The article points out the appearing and the first years of the Pedagogy Course of the Faculdade de Filosofia, Ciências e Letras de Rio Claro. It shows a general view of field research oriented by sociological studies and this influence in the process of graduation of the author as a educator